1967
DOI: 10.1143/jjap.6.214
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Investigations with a 500 kV Electron Microscope

Abstract: Metallurgical investigations such as recrystallization, martensitic transformation and dynamic behaviors of dislocations have been carried out with a 500 kV electron microscope. The critical foil thickness sufficient to observe the same dynamic behaviors of these phenomena as occurred in bulk specimens is about 1 µ for recrystallization in aluminum and iron alloys, and 3 µ for cell formation in aluminum. On the other hand, foil thickness which allows observation with the 500 kV electron microscope is practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1968
1968
2005
2005

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Although the major advantages of high voltage electron microscopy have now received some considerable attention, so far experimental data have been mainly limited to up to 1.2 MeV, e.g. studies of penetration (Dupouy & Perrier, 1962, 1964aFujita et al, 1967;Thomas, 1968;Hale & Henderson-Brown, 1970;Uyeda & Nonoyama, 1968;Humphreys et al, 1971), critical (disappearance) voltage phenomena (Uyeda, 1968;Bell, 1969;Lally et al, 1972), radiation damage (e.g. Makin, 1969;Urban & Wilkens, 1972;Thomas et al, 1970;Kobayashi & Ohara, 1966;Glaeser, 1971;Grubb & Groves, 1971;Claffey & Parsons, 1972), improvements in resolution of bright-field images of defects (Bell & Thomas, 1972;Goringe et al, 1972), and applications in materials science and biology (for reviews see for example Dupouy, 1968;Cosslett, 1970;Bell & Thomas, 1972;Fisher, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Although the major advantages of high voltage electron microscopy have now received some considerable attention, so far experimental data have been mainly limited to up to 1.2 MeV, e.g. studies of penetration (Dupouy & Perrier, 1962, 1964aFujita et al, 1967;Thomas, 1968;Hale & Henderson-Brown, 1970;Uyeda & Nonoyama, 1968;Humphreys et al, 1971), critical (disappearance) voltage phenomena (Uyeda, 1968;Bell, 1969;Lally et al, 1972), radiation damage (e.g. Makin, 1969;Urban & Wilkens, 1972;Thomas et al, 1970;Kobayashi & Ohara, 1966;Glaeser, 1971;Grubb & Groves, 1971;Claffey & Parsons, 1972), improvements in resolution of bright-field images of defects (Bell & Thomas, 1972;Goringe et al, 1972), and applications in materials science and biology (for reviews see for example Dupouy, 1968;Cosslett, 1970;Bell & Thomas, 1972;Fisher, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in scattering cross section leads to an increase in electron penetration with voltage. Thus for nonbiological research the main advantage of high voltage electron microscopy is the ability to observe thick materials (Dupouy and Perrier 1962a, b, Cosslett 1962, Fujita et al 1967, Uyeda and Nonoyama 1967. Consequently, it becomes possible to examine materials not easily observed in conventional 100 kvinstruments (e.g.…”
mentioning
confidence: 99%
“…Their results did not enable any conclusions to be drawn regarding the voltage dependence of the maximum transparency thickness, but dislocations could be observed in foils 3 p thick at 500 kv. Fujita et al (1967) carried out metallurgical investigations including a determination of the transmissive power for aluminium and stainless steel based on measurements of the mean absorption coefficient from wedge fringe profiles. They found that aluminium is about 2.3 times more transmissive than iron and showed that static images of dislocations could be obtainedfrom foils of about 8 p (Al) and 2 p (Fe) thick at 500 kv.…”
mentioning
confidence: 99%
“…In such a generally pessimistic atmosphere, the author and his group at the National Research Institute for Metals (NRIM) constructed in 1963-66 two practical double-tank-system 0.5 MV HVEMs in cooperation with Shimadzu, Ltd., 7), 16) as the author had already established that at least recrystallization occurs even in thin aluminum foils about 1 µm in thickness.…”
mentioning
confidence: 99%
“…In 1965, the author established the following as a result of his work with the 0.5 MV HVEMs: (1) the objective aperture angle must be increased with increasing accelerating voltage in order to take advantage of the simultaneous reflections, and then the value of t M increases almost linearly up to 0.5 MV, and (2) in-situ observation of the same phenomena as those in bulk materials becomes possible at 0.5 MV when the atomic number of the constituent atoms of the materials is less than about 20. 7) As a consequence of the author's pioneering work, about 60 HVEMs and ultraHVEMs have been installed, not only in Japan 13), 15) but in other countries as well, 18) as shown in the Appendix.…”
mentioning
confidence: 99%